Native American Nationalism and Nation Re-building Past and Present Cases - Poliandri, Simone (State University of New York Press, 2016)
Bringing together perspectives from a variety of disciplines, this book provides an interdisciplinary approach to the emerging discussion on Indigenous nationhood. The contributors argue for the centrality of nationhood and nation building in molding and, concurrently, blending the political, social, economic, and cultural strategies toward Native American self-definitions and self-determination. Included among the common themes is the significance of space-conceived both as traditional territory and colonial reservation-in the current construction of Native national identity. Whether related to historical memory and the narrativization of peoplehood, the temporality of indigenous claims to sovereignty, or the demarcation of successful financial assets as cultural and social emblems of indigenous space, territory constitutes an inalienable and necessary element connecting Native American peoplehood and nationhood. The creation and maintenance of Native American national identity have also overcome structural territorial impediments and may benefit from the inclusivity of citizenship rather than the exclusivity of ethnicity. In all cases, the political effectiveness of nationhood in promoting and sustaining sovereignty presupposes Native full participation in and control over economic development, the formation of historical narrative and memory, the definition of legality, and governance.